G125(P) Paediatric autoimmune neuropsychiatric disorders associated with streptococcus (PANDAS) and paediatric autoimmune neuropsychiatric syndrome (PANS) – current practice in the uk. (May 2019) - Ubhi, TU; Chmelova, KC; Brattan, SB; Curran, AC; Gupta, RG; Lim, ML
Abstract : Background: PANS and PANDAS are a group of disorders that are characterised by abrupt onset of obsessive compulsive disorder (OCD), tics, anxiety, enuretic problems and/or eating disorder. A subgroup of these conditions in prepubertal children, called PANDAS is associated with an autoimmune response after infection with Group A Streptococci (GAS). PANS and PANDAS were recently added to the WHO ICD-11 classification. Aims and method : We have created 2 surveys among parents to scope current practice and understanding in the UK. In the first cohort, we identified 112 patients with suspected PANS/PANDAS between the age 3 and 18 years. The aim of this survey was to obtain demographic data on this population of patients. In the second survey (98 children), we looked closer at current medical practice. Results: Most patients were started on antibiotics between 1–6 months after the onset of symptoms (44%). Co-Amoxiclav, Penicillin V and Azithromycin were among the most frequently used antibiotics. Anti-inflammatories were used in 70% of patients and IV immunoglobulins in 23% of patients. GPs were unfamiliar with this diagnosis in 90% of cases. Parents frequently described barriers in getting antibiotics and understanding of the condition. Conclusion: PANS and PANDAS are poorly recognised and treated conditions in the UK. New treatment guidelines from The UK PANDAS and PANS Physicians Network were published in May 2018 to help improve and standardise care. There is a need for clinical trial to provide hard evidence about PANS and PANDAS treatment in the UK in the future.